Comparative evaluation of interventional radiology modalities in treatment of liver abscess - Pandey, Jigyasa; Srivastava, Anurag (International Surgery Journal, 2018)
Background: Liver abscess (LA) is a superlative cavity in the liver resulting from the invasion and multiplication of microorganism. With progress of interventional radiology, alternative to surgery in form of percutaneous drainage (PD) have become popular. PD can be accomplished by either percutaneous catheter drainage (PCD) or percutaneous needle aspiration (PCNA). This study was conducted to assess the PD as a definitive treatment modality for LA and comparison of PCD and PCNA. Methods: The study was conducted in the Radiodiagnosis Department. All patients of LA were evaluated for age, sex, duration of complaints, type of intervention performed, and outcome etc. After diagnosis, patients were managed by PCD or PCNA. Response to treatment, duration of stay, and overall success of both the modalities were evaluated. Results: The duration of this study was 34 months. During this period, 57 patients were evaluated. Of total, 29 underwent PCD and 28 PCNA. Male to female ratio was 2:1. Right lobe was involved in 48. Mean volume of abscess cavity was 356.44 ml. All patients who underwent PCD responded to the treatment; however, 8 patients who were treated by PCNA did not respond completely. Outcome was statistically related to type of treatment modality. PCD was statistically superior to PCNA (P <0.05). Conclusions: PD may be regarded as first line of treatment for LA. It appears that PCD is better as compared to PCNA for successful outcome of patients.